Nota sobre la relación de Marion con Levinas - Sebbah, François-David (2024)
This article aims to assess the relevance of Jean Luc Marion’s reading of Levinas’ “ethical relation”. The Levinasian gesture, which could be deployed in several senses, is located at the very heart of the “French moment of Phenomenology”.